Little & Lion - Colbert, Brandy (Little, Brown and Company, 2018)
Suzette returns home to Los Angeles from boarding school and grapples with her bisexual identity when she and her stepbrother Lionel fall in love with the same girl. As Lionel's bipolar disorder begins to spin out of control, it forces Suzette to confront her own demons. Can she save Lionel from himself-- and will he trust her enough to do so?
"A novel"--Jacket
Originally published in hardcover and ebook by Little, Brown and Company in August 2017.
Keywords: Brothers and sisters / Juvenile fiction; Families / Juvenile fiction; Bisexuality / Juvenile fiction; Manic-depressive illness / Juvenile fiction; Young adult fiction; Brothers and sisters / Fiction; Family life / California / Fiction; Dating (Social customs) / Fiction; Bisexuality / Fiction; Manic-depressive illness / Fiction; Mental illness / Fiction; YOUNG ADULT FICTION / Family / Alternative Family; YOUNG ADULT FICTION / Family / Siblings; YOUNG ADULT FICTION / Girls & Women; YOUNG ADULT FICTION / LGBT.; YOUNG ADULT FICTION / School & Education / Boarding School & Prep School; YOUNG ADULT FICTION / Social Themes / Dating & Sex; YOUNG ADULT FICTION / Social Themes / Mental Illness; YOUNG ADULT FICTION / Social Themes / Prejudice & Racism; Bisexuality; Brothers and sisters; Families; Manic-depressive illness; Manisch-depressive Krankheit; Schwester; Hermaphroditismus; Psychose; Familie; Bruder; California / Fiction; Kalifornien; Jugendbuch